The mountain environment, a driver for adaptation to climate change. (November 2015) - Delay, Etienne; Piou, Cyril; Quenol, Hervé
Highlights: Is the mountain environment a potential adaption to climate change in vine-growing? Based on observations we explored territorial dynamics using agent-based modeling. The cooperative influenced vine-growers through a bonus/malus factor on acidity. Cooperative incentives spatially structure the vine-growing territory. Conflicts among social and individual interests limit adaptation to climate change. Abstract: The mountain environment is perceived today by vine-growers as a strong structural constraint. Yet in the current context of climate change, in which we turn to genetics, irrigation or innovation in cultural practices to maintain production quality, could the mountain environment emerge as a solution for adapting to climate change in vine-growing? Here we explore the role of cooperative policies that may be deployed on the territorial scale, using an agent-based model. Our model was based on the viticulture of the Banyuls–Collioures AOC area, which is characterized by small-scale vine-growers and marked by widespread involvement in cooperative systems. The simulation results showed an important role of cooperative policies not only to conserve narrow production window and required vine quality, but also in respect of the emblematic landscape structure. These results should foster vine-growers to strengthen their cooperatives and adequately use these organizations to mitigate future climate change impacts.